Profil Mood Atlet Pra-PON Sepak Takraw Puteri Sulawesi Tengah Dalam Melakukan Latihan - Wahyudhi, Andi Sultan Brilin Susandi Eka; Fajarwati, Sri (UIR Press, 2020)
The research was conducted to find out how much the mood of female pre-PON sepak takraw athletes in Sulawesi Tengah after doing the exercises and how the mood condition of the female pre-PON athletes after conducting the training. The method in this research is a survey research. The population of this study is 10 people, namely the pre-PON Sepak Takraw athletes of the women of Sulawesi Tengah with the sampling technique using total sampling. The collecting technique of data is a questionnaire using the rating scale. The results showed that fatigue indicators were 10% very low category, angry mood indicators were 24% very low category, ready feeling indicators were 54% good categories, tension indicators were 23.14% very low categories, self-assessment indicators were 40.85% low category, confused mood indicators were for 26.28% low category, and depression indicators were 6.85% very low category. Meanwhile, mood of the female athletes of sepak takraw is in a ready condition, this is based on the results of the ready feeling amount 54% with the high category. The conclusion is that the indicators of fatigue, anger, tension, self-assessment, confusion, depression are all in the very low categories, mean that even though the sepak takraw athletes do exercise every day and do not conduct match trials, they can still handle the psychological condition well. Meanwhile, the feeling ready indicators of the sepak takraw athletes have a high category.